Reduction in Lp(a) after a medically supervised, prolonged water-only fast followed by a whole-plant-food diet free of added salt, oil, and sugar: a case report - Thompson, Natasha; Streutker, Anthony; Goldhamer, Alan C.; Myers, Toshia R. (Frontiers in Nutrition, 2024)
Lipoprotein(a) [Lp(a)] is a low-density lipoprotein (LDL) associated with increased cardiovascular disease (CVD) risk. High Lp(a) levels are genetically determined and lack effective pharmacotherapy. This report describes the case of a 67-year-old, vegan male with high CVD risk who underwent a 10-day, medically supervised water-only fast followed by a sixweek SOS-free diet (free of added salt, oil, and sugar). At the six-week-follow-up visit, he experienced significant reductions in several CVD risk markers, including blood pressure, total cholesterol, LDL, high-sensitivity C-reactive protein, and a 39% decrease in Lp(a), from 236.3 nmol/L to 143.4 nmol/L. This decrease is comparable to reductions achieved with PCSK9 inhibitors. These findings suggest that prolonged water-only fasting and/or an SOS-free diet may be an effective alternative approach for managing high Lp(a) levels and reducing CVD risk in a vegan population, warranting further research..